Proposals for experimental study of wakefield undulator radiation - Opanasenko, A.N. (Вопросы атомной науки и техники, 2006)
The possibility of detection of a wake-field undulator radiation generated by short bunches of relativistic charged particles, moving through a periodic rf structure, is estimated.